KEANEKARAGAMAN FITOPLANKTON DI KOLAM RETENSI KAMBANG IWAK KOTA PALEMBANG - Wahyuni, Intan Sri; Rosanti, Dewi (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2016)
Research of Phytoplankton Diversity in Kambang Iwak Palembang retension pond, was in May to June 2016. The research objective was to determine the diversity of phytoplankton in Palembang Iwak Kambang retention pond. The study used survey method with purposive sampling method, samples were taken from five stations is determined by filtering 40 liters of water at each station. Furthermore, the type and amount of phytoplankton. The results showed that the diversity of phytoplankton consists of 4 classes Chlorophyceae, Bacillariophyceae, Euglenophyceae and Cyanophyceae. 11 orders, 14 familia, 16 genera and 16 species. Abundance of phytoplankton with the lowest density values were 9.37 ind / liter (station 5), while the highest value of 28.71 ind / liter (station 3). Dominance index the highest in station 5 with a value of 0.36 and the lowest value at station 4 with a value of 0.19. Diversity index of the five observation stations classified as moderate by the respective value of 1.59 (Station 1), 1.41 (2 stations), 1.89 (3 stations), 1.79 (4 stations) and 1.19 (the station 5).Keywords : phytoplankton, diversity, retention ponABSTRAK Penelitian berjudul Keanekaragaman Fitoplankton di Kolam Retensi Kambang Iwak Palembang, telah dilaksanakan pada Mei sampai Juni 2016, bertujuan untuk mengetahui keanekaragaman fitoplankton di sana. Penelitian menggunakan metode survey dengan cara purpossive sampling. Sampel fitoplankton diambil dari 5 stasiun dengan menyaring air sebanyak 40 liter pada tiap stasiun. Selanjutnya dilakukan pengindetifikasian jenis dan jumlah fitoplankton. Hasil menunjukkan bahwa keanekaragaman fitoplankton terdiri dari 4 kelas Chlorophyceae, Bacillariophyceae, Euglenophyceae dan Cyanophyceae. 11 ordo, 14 familia, 16 genus dan 16 spesies. Kelimpahan fitoplankton dengan nilai densitas yang terendah 9,37 ind/liter (pada stasiun 5), sedangkan nilai tertinggi 28,71 ind/liter (pada stasiun 3). Indeks dominansi yang tertinggi pada stasiun 5 dengan nilai 0,36 dan nilai terendah pada stasiun 4 dengan nilai 0,19. Indeks keanekaragaman dari kelima stasiun pengamatan tergolong sedang dengan nilai masing-masing 1,59 (stasiun 1), 1,41 (stasiun 2), 1,89 (stasiun 3), 1,79 (stasiun 4) dan 1,19 (stasiun 5).Kata kunci : keanekaragaman, fitoplankton, kolam retensi